Evaluation of antihyperlipidemic potential of dendrobium officinale combined with camellia hakodae in poloxamer-407-induced experimental model of mice - Yen, Pham Hai; Anh, Pham Thi Van; Ha, Nguyen Thi Thanh; Trang, Tran Quynh; Hong, To Le; Hien, Dang Thi Thu (Tạp chí Nghiên cứu Y học, 2026)
Herbal medicine has been used in folk medicine in many parts of the world due to its potential medicinal properties. This study was conducted to evaluate the antihyperlipidemic effects of a natural-derived combination of Dendrobium officinale and Camellia hakodae, abbreviated as VHL, in a Poloxamer 407-induced hyperlipidemia model in Swiss mice. An endogenous hyperlipidemia model was established by intraperitoneal administration of Poloxamer-407 at 200 mg/kg body weight. The VHL extract was administered at doses of 1.14 and 3.42 g/kg body weight, once daily for seven consecutive days. At the end of the study, serum lipid parameters were determined. The results show that serum levels of total cholesterol (TC), triglycerides (TG), and non-high-density lipoprotein cholesterol (Non-HDL-C) were significantly increased in poloxamer 407-induced hyperlipidemic control mice. In contrast, TG parameters were markedly reduced in mice treated with the VHL capsules at 1.44 g/kg body weight and 3.42 g/kg body weight. VHL also improved serum HDL-C levels and trendedd to reduce TC and non-HDL-C compared to the cholesterol control group. In conclusion, a naturally derived combination of Dendrobium officinale and Camellia hakodae showed TG-lowering potential and may help prevent hypercholesterolemia in a P407-induced hyperlipidemia model.